Buckling Dielectric Elastomer Actuator
By using a dielectric elastomer material film formed by random block copolymerization, the problems of insufficient response speed, recovery time and positioning accuracy of existing actuators are solved, and more efficient actuation performance and flexible integration capabilities are achieved.
Patent Information
- Application Number
- CN201980081065.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-10-09
- Filing Date
- 2019-10-09
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2039-10-09
AI Technical Summary
Existing dielectric elastomeric actuators have shortcomings in response speed, recovery time and positioning accuracy, and are difficult to integrate into soft and flexible tactile devices.
A dielectric elastomer material film formed by random block copolymerization of a polymer material including silicon or nitrogen atoms with an acrylate or vinyl end group and a polar polymer material is used as the dielectric elasticity of the buckling actuator body material. The material modulates the properties of the copolymer film by varying the amount of polar polymer material, improving the static and dynamic characteristics of the actuator.
This achieves faster actuation response and recovery times, reduces actuation drift, improves positioning accuracy, and allows actuators to be integrated on soft substrates for a variety of applications.
Smart Images

Figure CN113272981B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a buckling dielectric elastomer actuator comprising a film of dielectric elastomer material, a dielectric elastomer material and a method of forming the dielectric elastomer material. Background Art
[0002] The listing or discussion of a previously published document in this specification should not necessarily be taken as an admission that the document is part of the state of the art or is common general knowledge.
[0003] The sense of touch is extremely involved in any physical interaction we encounter in our daily lives. However, when interacting with a virtual environment, this sense of touch is often insufficient. Fortunately, with haptic technology, the sense of touch can be recreated for human-computer or human-machine interaction by using haptic devices such as actuators to recreate the forces that stimulate the desired sensation on the skin. As haptic technology integrates into our lives, applications such as enhanced surgical training, video games, and Braille displays for the blind are now becoming a reality.
[0004] Currently, materials such as piezoelectric ceramics, shape memory alloys, and electroactive polymers have been applied as actuators for tactile feedback devices. However, the actuation strain achieved by piezoelectric ceramics is typically less than 1%, while the actuation of shape memory alloys is difficult to control due to their nonlinear thermomechanical properties. As such, electroactive polymers (EAPs) remain as the preferred material for tactile feedback due to their low power consumption, light weight, low cost, and high actuation strain. EAPs are a class of materials that can exhibit changes in size and shape when an electric field is applied.
[0005] Among this category of materials, dielectric elastomers (DE) are one of the preferred choices for haptic devices due to their fast actuation response, quiet operation, and long-term performance at room temperature. In addition, dielectric elastomers (DE) have low elastic modulus, high strain capacity, and excellent resilience, allowing them to be used in a variety of applications.
[0006] Dielectric elastomer is an example of EAP. Common DE materials include 3M's acrylic-based adhesive film (called VHB series). These VHB polymers have excellent properties, including the ability to achieve an elongation of more than 600% and an area actuation strain of up to 380%. However, these materials, due to their high viscoelastic properties, exhibit slow response and recovery times, typically hundreds of seconds. In addition, as a dissipative process, viscoelastic hysteresis has been shown to have an adverse effect on performance and cause inaccurate positioning. In this way, materials with low viscoelasticity such as silicone rubber are often used to replace VHB polymers. However, these materials often exhibit a low dielectric constant (≈2.8), which is not enough to achieve high strain in dielectric elastomer actuators. Alternatively, DE can be pre-stretched to reduce the influence of viscoelasticity. Some studies have shown that pre-stretching provides benefits such as shorter relaxation time, reduced drift effect and higher electromechanical strain. However, the pre-stretched state is often achieved by mounting the DE film on a rigid frame, which increases the weight of the actuator and limits the integration of such actuators into a soft and flexible body. Furthermore, pre-stretching reduces the lifetime of the device due to stress relaxation and fatigue.
[0007] A common type of actuator used for tactile and refreshable Braille displays is the buckling mode actuator. These actuators exhibit out-of-plane deflection when a voltage is applied across the DE. However, in order to induce this actuation mode, the DE must be constrained by a rigid boundary (such as a rigid ring or frame) to prevent area expansion. In addition, it has been reported that in order to achieve unidirectional buckling, pre-bending is required on the inactive DE, which can be achieved by air pressure or geometric support. However, such an increase in component / forming forces may limit the integration of buckling actuators into soft and flexible tactile devices.
[0008] In view of the above, there is still a need to develop new materials or actuators to solve one or more of the above problems. More importantly, such materials or actuators need to have excellent dielectric and mechanical properties and be able to allow repeated use. In addition, they must be highly stable, but also versatile, so that they can be easily integrated into wearable technology for different applications. Summary of the invention
[0009] Aspects and embodiments of the invention will be described by reference to the following numbered clauses.
[0010] 1. A buckling actuator comprising:
[0011] a first electrode;
[0012] a second electrode; and
[0013] A dielectric elastomer material film having a first surface and a second surface sandwiched between the first and second electrodes, the material being formed by random block copolymerization of:
[0014] a polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups; and
[0015] Polar polymeric materials having two or more acrylate or vinyl end groups
[0016] in:
[0017] The first electrode is arranged to cover a first electrode area on the first surface of the dielectric elastomer material film, and the second electrode is arranged to cover a second electrode area on the second surface of the dielectric elastomer material film, so that there is an overlapping area between the first and second electrode areas, and the area has an area smaller than the area of the first or second surface of the dielectric elastomer material film.
[0018] 2. An actuator according to clause 1, wherein the first and second electrode areas each occupy 5% to 50%, such as 10 to 40%, such as 15 to 30% of the area on the first and second surfaces of the dielectric elastomer material film, respectively.
[0019] 3. An actuator according to clause 1 or clause 2, wherein:
[0020] (a) the polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups has two acrylate end groups; and / or
[0021] (b) The polar polymer material having two or more acrylate or vinyl terminal groups has two acrylate terminal groups.
[0022] 4. An actuator according to any of the preceding clauses, wherein the polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups is selected from one or more of the following: a urethane acrylate polymer material having two acrylate end groups, poly(dimethylsiloxane) dimethacrylate, and a thermoplastic polyurethane having two acrylate end groups.
[0023] 5. An actuator according to claim 4, wherein the urethane acrylate polymer material having two acrylate end groups is an aliphatic acrylate polymer material having two acrylate end groups, optionally wherein the aliphatic acrylate polymer material having two acrylate end groups is selected from one or more of CN310, CN8881, CN8884, CN8888, CN9004, CN9014, CN9028, CN9031, CN9002, CN966J75, CN9018, CN9021, CN3108, CN3211 and CN8004, optionally wherein the urethane acrylate polymer material having two acrylate end groups is CN9021.
[0024] 6. An actuator according to any of the preceding clauses, wherein the polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups has a number average molecular weight greater than 20,000 Daltons, such as 20,001 to 50,000 Daltons.
[0025] 7. An actuator according to any of the preceding clauses, wherein the polar polymer material having two or more acrylate or vinyl end groups is selected from one or more of the following: poly(ethylene glycol) diacrylate (PEGDA), poly(caprolactone) dimethacrylate and poly(propylene glycol) dimethacrylate.
[0026] 8. The actuator of clause 7, wherein the polar polymer material having two or more acrylate or vinyl end groups is poly(ethylene glycol) diacrylate (PEGDA).
[0027] 9. An actuator according to any of the preceding clauses, wherein the polar polymer material having two or more acrylate or vinyl end groups has a number average molecular weight of 200 to 1,000 Daltons.
[0028] 10. An actuator according to clause 9, wherein the polar polymer material having two or more acrylate or vinyl end groups has a number average molecular weight of 250 to 750 Daltons, such as 400 to 600 Daltons, such as 575 Daltons.
[0029] 11. An actuator according to any of the preceding clauses, wherein the polar polymer material having two or more acrylate or vinyl end groups is present in the dielectric elastomeric material in an amount of 5 to 15 wt%, such as 10 to 15 wt%.
[0030] 12. An actuator according to any of the preceding clauses, wherein:
[0031] (aa) The dielectric elastomer material has a dielectric constant (ε r ) is greater than 3, such as 3.1 to 100, such as 5.8 to 20, such as 6 to 15, such as 6.2 to 9.4; and / or
[0032] (ab) the dielectric elastomeric material has an elastic modulus of 0.1 to 4 MPa, such as 0.3 to 4 MPa; and / or
[0033] (ac) the flexure actuator has a displacement less than or equal to 1,250 μm, such as 100 to 1,250 μm, such as 500 to 1,250 μm, such as 250 to 750 μm, such as 1,000 to 1,250 μm, when a voltage is supplied to the first and second electrodes; and / or
[0034] (ad) the dielectric elastomeric material has a dielectric breakdown less than or equal to 30 V / μm, such as 10 V / μm to 25 V / μm, such as 8 V / μm to 25 V / μm, such as 10 V / μm to 20 V / μm; and / or
[0035] (ae) The dielectric elastomeric material has an elongation at break greater than 50%, such as 50 to 960%, such as 50 to 500%, such as 150 to 450%, such as 423%.
[0036] 13. An actuator according to any of the preceding clauses, wherein the actuator further comprises a flexible substrate, wherein the second electrode is placed on the flexible substrate, and the dielectric elastomer material film is formed on top of the flexible substrate and at least a portion of the second electrode.
[0037] 14. An actuator according to any of the preceding clauses, wherein the actuator does not comprise a rigid constraining member, optionally wherein when a voltage is applied, the actuator is capable of out-of-plane actuation in the absence of a rigid constraining member.
[0038] 15. An actuator according to any of the preceding clauses, wherein the first and second electrodes are independently selected from carbon grease, one or more metal nanowires, hydrogels, ion gels, carbon nanotubes and liquid metals, optionally wherein the first and second electrodes are formed by silver nanowires.
[0039] 16. An actuator according to any of the preceding clauses, wherein the actuator is transparent.
[0040] 17. A dielectric elastomeric material formed by random block copolymerization of:
[0041] a polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups; and
[0042] A polar polymeric material having two or more acrylate or vinyl terminal groups.
[0043] 18. A dielectric elastomeric material according to clause 17, wherein:
[0044] (ai) the polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups has two acrylate end groups; and / or
[0045] (bii) The polar polymer material having two or more acrylate or vinyl terminal groups has two acrylate terminal groups.
[0046] 19. A dielectric elastomer material according to clause 17 or clause 18, wherein the polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups is selected from one or more of the following: a urethane acrylate polymer material having two acrylate end groups, poly(dimethylsiloxane) dimethacrylate, and a thermoplastic polyurethane having two acrylate end groups.
[0047] 20. The dielectric elastomer material according to claim 19, wherein the urethane acrylate polymer material having two acrylate end groups is an aliphatic acrylate polymer material having two acrylate end groups, optionally wherein the aliphatic acrylate polymer material having two acrylate end groups is selected from one or more of CN310, CN8881, CN8884, CN8888, CN9004, CN9014, CN9028, CN9031, CN9002, CN966J75, CN9018, CN9021, CN3108, CN3211 and CN8004, optionally wherein the urethane acrylate polymer material having two acrylate end groups is CN9021.
[0048] 21. A dielectric elastomeric material according to any one of clauses 17 to 20, wherein the polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups has a number average molecular weight greater than 20,000 Daltons, such as 20,001 to 50,000 Daltons.
[0049] 22. A dielectric elastomeric material according to any one of clauses 17 to 21, wherein the polar polymer material having two or more acrylate or vinyl end groups is selected from one or more of the following: poly(ethylene glycol) diacrylate (PEGDA), poly(caprolactone) dimethacrylate and poly(propylene glycol) dimethacrylate.
[0050] 23. The dielectric elastomeric material of clause 22, wherein the polar polymer material having two or more acrylate or vinyl end groups is poly(ethylene glycol) diacrylate (PEGDA).
[0051] 24. The dielectric elastomeric material of any one of clauses 17 to 23, wherein the polar polymeric material having two or more acrylate or vinyl end groups has a number average molecular weight of from 200 to 1,000 Daltons.
[0052] 25. A dielectric elastomeric material according to clause 24, wherein the polar polymer material having two or more acrylate or vinyl end groups has a number average molecular weight of 250 to 750 Daltons, such as 400 to 600 Daltons, such as 575 Daltons.
[0053] 26. A dielectric elastomeric material according to any one of clauses 17 to 25, wherein the polar polymeric material having two or more acrylate or vinyl end groups is present in the dielectric elastomeric material in an amount of 5 to 15 wt%, such as 10 to 15 wt%.
[0054] 27. A dielectric elastomeric material according to any one of clauses 17 to 26, wherein:
[0055] (Aa) The dielectric elastomer material has a dielectric constant (ε r ) is greater than 3, such as 3.1 to 100, such as 5.8 to 20, such as 6 to 15, such as 6.2 to 9.4; and / or
[0056] (Ab) the dielectric elastomeric material has an elastic modulus of 0.1 to 4 MPa, such as 0.3 to 4 MPa; and / or
[0057] (Ac) the dielectric elastomer material is provided in the form of a film; and / or
[0058] (Ad) the dielectric elastomeric material has a dielectric breakdown less than or equal to 30 V / μm, such as 10 V / μm to 25 V / μm, such as 8 V / μm to 25 V / μm, such as 10 V / μm to 20 V / μm; and / or
[0059] (Ae) The dielectric elastomeric material has an elongation at break greater than 50%, such as 50 to 960%, such as 50 to 500%, such as 150 to 450%, such as 423%.
[0060] 28. A method of forming a dielectric elastomeric material as described in any one of clauses 17 to 27, the method comprising the steps of:
[0061] (i) providing a mixture comprising a polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups and a polar polymer material having two or more acrylate or vinyl end groups in the presence of a free radical initiator and optionally in the presence of a solvent; and
[0062] (ii) reacting the mixture at an elevated temperature for a period of time to provide the dielectric elastomeric material.
[0063] 29. A method according to clause 28, wherein:
[0064] (ia) the polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups has two acrylate end groups; and / or
[0065] (ib) The polar polymer material having two or more acrylate or vinyl terminal groups has two acrylate terminal groups.
[0066] 30. A method according to clause 28 or clause 29, wherein the polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups is selected from one or more of the following: a urethane acrylate polymer material having two acrylate end groups, poly(dimethylsiloxane) dimethacrylate, and a thermoplastic polyurethane having two acrylate end groups.
[0067] 31. A method according to clause 30, wherein the urethane acrylate polymer material having two acrylate end groups is an aliphatic acrylate polymer material having two acrylate end groups, optionally wherein the aliphatic acrylate polymer material having two acrylate end groups is selected from one or more of CN310, CN8881, CN8884, CN8888, CN9004, CN9014, CN9028, CN9031, CN9002, CN966J75, CN9018, CN9021, CN3108, CN3211 and CN8004, optionally wherein the urethane acrylate polymer material having two acrylate end groups is CN9021.
[0068] 32. A method according to any one of clauses 28 to 31, wherein the polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups has a number average molecular weight greater than 20,000 Daltons, such as 20,001 to 50,000 Daltons.
[0069] 33. A method according to any one of clauses 28 to 32, wherein the polar polymer material having two or more acrylate or vinyl end groups is selected from one or more of the following: poly(ethylene glycol) diacrylate (PEGDA), poly(caprolactone) dimethacrylate and poly(propylene glycol) dimethacrylate.
[0070] 34. The method of clause 33, wherein the polar polymeric material having two or more acrylate end groups is poly(ethylene glycol) diacrylate (PEGDA).
[0071] 35. A method according to any one of clauses 28 to 34, wherein the polar polymeric material having two or more acrylate or vinyl end groups has a number average molecular weight of from 200 to 1,000 Daltons.
[0072] 36. A method according to clause 35, wherein the polar polymeric material having two or more acrylate or vinyl end groups has a number average molecular weight of 250 to 750 Daltons, such as 400 to 600 Daltons, such as 575 Daltons.
[0073] 37. A method according to any one of clauses 28 to 36, wherein the polar polymeric material having two or more acrylate or vinyl end groups is present in the dielectric elastomeric material in an amount of 5 to 15 wt%, such as 10 to 15 wt%.
[0074] 38. A method according to any one of clauses 28 to 37, wherein after completion of step (ii) of clause 28, the dielectric elastomeric material is provided in the form of a film.
[0075] 39. A method according to any one of clauses 28 to 38, wherein the mixture of step (i) of clause 28 further comprises a solvent, wherein the solvent and the polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups have a weight to weight ratio of 10:1 to 1:1, such as 3:1 to 1:1, optionally wherein the solvent is acetone and / or isopropanol.
[0076] 40. A method according to any one of clauses 28 to 39, wherein:
[0077] (A) the elevated temperature in step (ii) of clause 28 is from 50 to 100°C, such as from 70 to 90°C;
[0078] (B) the free radical initiator is present in an amount of at least 1 wt % (e.g., 1 wt % to 10 wt %, such as 1 wt % to;
[0079] (C) The time period of the reaction in step (ii) of Item 28 is 10 minutes to 24 hours, such as 15 minutes to 12 hours, such as 20 minutes to 1 hour, such as 30 minutes.
[0080] 41. An array of buckling actuators comprising a plurality of buckling actuators as described in any one of clauses 1 to 16.
[0081] 42. An array of buckling actuators according to clause 41, wherein the array of buckling actuators is arranged in a cross-junction configuration. BRIEF DESCRIPTION OF THE DRAWINGS
[0082] Figure 1 Depicted are: (a) and (b) the molecular structures of polyurethane acrylate (PUA, CN9021) and polyethylene glycol diacrylate (PEGDA), respectively, used to synthesize the copolymer membrane of the present invention.
[0083] Figure 2 Depicted are FTIR spectra of: (a) an initial batch; and (b) subsequent batches of pristine PUA (CN9021) and PUA-PEGDA copolymer films of the present invention.
[0084] Figure 3 Depicted are the dielectric constants of: (a) the initial batch; and (b) subsequent batches of PUA and PUA-PEGDA copolymer films (5, 10 and 15 wt%), measured at 1 kHz. For each concentration of PEGDA, three samples were measured.
[0085] Figure 4 Depicted are the dielectric constants of: (a) initial batch; and (b) subsequent batches of PUA, PUA-PEGDA copolymer films (0, 5, 10 and 15 wt % PEGDA), and VHB 4905 (for subsequent batches only), measured in the frequency range of 1 kHz to 1 MHz.
[0086] Figure 5 Plotted are stress-strain curves of PUA and PUA-PEGDA copolymer films (5, 10, and 15 wt % PEGDA) for: (a) the initial batch; and (b) subsequent batches, measured by standard tensile testing at 3.33 mm s -1The inset image in (b) shows the magnification at low tensile strains between 0 and 200%.
[0087] Figure 6 Depicted are loading and unloading cycle tests performed on an initial batch of: (a) PUA; (b) PUA-PEGDA-5; (c) PUA-PEGDA-10; and (d) PUA-PEGDA-15 at 3.33 mm s -1 The strain rate of 10000 nm was applied for 10 cycles (maximum strain of 50%), showing the hysteresis behavior of the copolymer film.
[0088] Figure 7 Depicted are loading and unloading cycle tests performed on subsequent batches of: (a) PUA; (b) PUA-PEGDA-5; (c) PUA-PEGDA-10; and (d) PUA-PEGDA-15, at 1 mm s -1 30 cycles at a strain rate of 100 % (maximum strain of 100%) showed a reduction in hysteresis losses.
[0089] Figure 8 Depicted are: (a) a schematic diagram of a dielectric actuator (DEA) (10) according to the present invention; (b) a layered arrangement of the DEA on a substrate (30); (c) a cross-sectional view AA of the DEA (10) in (a); and (d) a photograph of the DEA of the present invention.
[0090] Fig. 9 Depicted are the actuation of a single buckling mode dielectric elastomer actuator (DEA) in the (a) off state; and (b) on state, where Δh represents the displacement achieved when voltage is applied; (c) representative area strains of PUA and PUA-PEGDA copolymers (5, 10, and 15 wt% PEGDA) with increasing electric field strength; and (d) estimated work density based on the measured area strains of PUA and PUA-PEGDA copolymers (5, 10, and 15 wt% PEGDA) with increasing electric field strength.
[0091] Fig.10 Depicted are the area strain of the following individual samples as the electric field increases: (a) PUA; (b) PUA-PEGDA-5; (c) PUA-PEGDA-10; and d) PUA-PEGDA-15.
[0092] Fig.11 Depicted are representative flexural strains of PUA and PUA-PEGDA copolymers (5, 10, and 15 wt% PEGDA) as the electric field increases.
[0093] Fig.12The electromechanical sensitivity of PUA and PUA-PEGDA copolymers (5, 10, and 15 wt% PEGDA) as a function of temperature from -40°C to 100°C is depicted.
[0094] Fig.13 Depicted are: (a) photographs of DEA fabricated with an initial batch of PUA-PEGDA-10 copolymer membranes with carbon grease electrodes in the on and off states. The dashed line indicates the initial position of the laser spot in the "off" state, while the bottom dashed line in the "on" state photograph indicates the final position of the membrane; and (b) the initial PUA-PEGDA-10 vertical deflection of as-fabricated DEA at 0.1 Hz in response to an applied voltage of 8 kV against time.
[0095] Fig.14 Depicted are: (a) normalized displacement of DEA made from an initial batch of PUA-PEGDA copolymer films (0, 5, 10, and 15 wt % PEGDA) versus applied voltage; and (b) vertical deflection of the initial PUA-PEGDA copolymer films (0, 5, 10, and 15 wt % PEGDA) over time at 0.1 Hz in response to an applied voltage of 8 kV.
[0096] Fig.15 Depicted: (a) 0.1 Hz at 10 V μm -1 (a) Profile of a single cycle of strain response of DEA (made from the initial batch of PUA and PUA-PEGDA copolymer (0, 5, 10, and 15 wt% PEGDA)) under electric field; and (b) response time and recovery time of DEA (made from the initial batch of PUA and PUA-PEGDA copolymer membrane (0, 5, 10, and 15 wt% PEGDA)) when voltage is applied and removed, respectively.
[0097] Fig.16 Depicted are: (a-d) DEA made from subsequent batches of PUA, PUA-PEGDA-5, PUA-PEGDA-10, and PUA-PEGDA-15, respectively, at 10 V μm -1 The first 145 cycles of the cyclic test performed at a frequency of 0.5 Hz under an electric field strength of 10 kV μm. The approximate drift distance after 145 cycles is indicated in each figure; (e) at 10 kV μm -1 Profile of a single cycle of strain response of PUA and PUA-PEGDA-15 under electric field at 0.1 Hz, showing the response time t 0.9 The response time t 0.9represents the time for DEA to reach 90% of its maximum displacement at 0.1 Hz; and (f) the response time (t) of DEA prepared with subsequent copolymer membranes of various PEGDA concentrations (0, 5, 10, and 15 wt%). 0.9 ).
[0098] Fig.17 Depicted is the DEA fabricated from subsequent batches at 10 V μm -1 Cycle life tests for 1050 cycles (0 to 145 cycles, and 900 to 1050 cycles) at 0.5 Hz frequency under an electric field of : (a, b) PUA; (c, d) PUA-PEGDA-5; (e, f) PUA-PEGDA-10; and (g, h) PUA-PEGDA-15. The approximate displacement achieved is indicated in each figure.
[0099] Fig.18 Depicted are: (a) photographs of flexible DEA fabricated using PUA-PEGDA-10 copolymer film (with carbon grease electrodes) mounted on a flexible PET substrate; (b) normalized displacement of flexible DEA versus different bending radii; and (c) displacement of flexible DEA within 30 cycles at different bending radii.
[0100] Fig.19 Depicted are: (a) a schematic diagram of an as-fabricated DEA array with multiple electrodes in a cross-junction configuration. Electrical connections are connected to activate the middle three regions at 52; (b) a top view showing the arrangement of the DEA array; and (c) a demonstration of the operation of an as-fabricated DEA using a PUA-PEGDA-15 copolymer film. The electrical connections are connected in such a way that the middle junctions are activated. The array is subjected to 12 V μm at approximately 0.4 Hz. -1 The electric field.
[0101] Fig. 20 Depicted are: (a) integration of an as-fabricated DEA array into a watchband to provide tactile feedback for a wearable device; (b) a top view showing the arrangement of the DEA array such that selected actuation is at the overlapping cross-junctions (52) between the top and bottom electrodes under electrical connection; and (c) demonstration of tactile feedback using an as-fabricated DEA array using a PUA-PEGDA-15 copolymer film.
[0102] Fig.21Depicted are: (a) photographs of DEA fabricated with PUA-PEGDA-10 copolymer films with silver nanowire electrodes in the on and off states. The dashed line indicates the initial position of the laser spot in the off state, while the bottom dashed line in the "on" state photograph indicates the final position of the film; and (b) the initial PUA-PEGDA-10 vertical deflection of as-fabricated DEA at 0.1 Hz in response to an applied voltage of 8 kV against time; and (c) the optical transmittance of PUA-PEGDA copolymer films with and without silver nanowire electrodes in the visible light range of 400-800 nm.
[0103] Fig. 22 Depicted is the -1 Stress-strain curves of PUA, PUA-PEGDA-15 and PUA-PEGDA(2000)-15 copolymer films determined by standard tensile testing at a strain rate of 1.5 Å. DETAILED DESCRIPTION
[0104] It has been surprisingly found that random block copolymerization of a polymer material including silicon or nitrogen atoms (e.g., polyurethane acrylate) having two or more acrylate or vinyl end groups with a polar polymer material (e.g., polyethylene glycol diacrylate) having two or more acrylate or vinyl end groups produces a random block copolymer film having excellent dielectric and mechanical properties. Incorporation of such a copolymer film into a dielectric elastomer actuator improves the static and dynamic properties of the actuator (i.e., minimal actuation drift, faster actuation response and recovery time). Advantageously, the properties of the copolymer film can be adjusted accordingly for different applications by varying the amount of the polar polymer material having two or more acrylate or vinyl end groups. Transparent actuators can also be obtained using any suitable transparent or less optically absorbing electrodes.
[0105] Therefore, in a first aspect of the present invention, there is provided a buckling actuator comprising:
[0106] a first electrode;
[0107] a second electrode; and
[0108] A dielectric elastomer material film having a first surface and a second surface sandwiched between the first and second electrodes, the material being formed by random block copolymerization of:
[0109] a polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups; and
[0110] Polar polymeric materials having two or more acrylate or vinyl end groups
[0111] in:
[0112] The first electrode is arranged to cover a first electrode area on the first surface of the dielectric elastomer material film, and the second electrode is arranged to cover a second electrode area on the second surface of the dielectric elastomer material film, so that there is an overlapping area between the first and second electrode areas, and the area has an area smaller than the area of the first or second surface of the dielectric elastomer material film.
[0113] In the embodiments herein, the word "comprising" may be interpreted as requiring the mentioned features, but not limiting the presence of other features. Alternatively, the word "comprising" may also refer to situations in which only the listed components / features are intended to be present (e.g., the word "comprising" may be replaced by the phrase "consisting of" or "consisting essentially of". It is expressly contemplated that both the broader and narrower interpretations may apply to all aspects and embodiments of the present invention. In other words, the word "comprising" and its synonyms may be replaced by the phrase "consisting of" or the phrase "consisting essentially of" or their synonyms, and vice versa.
[0114] As used herein, the term "buckling actuator" is intended to refer to a buckling mode actuator which requires the components listed above, but which may also include additional components. A buckling mode actuator exhibits out-of-plane deflection when a voltage is applied across a dielectric elastomer (DE) forming part of the actuator.
[0115] As used herein, the terms "first electrode" and "second electrode" are intended to refer to the conductive material placed on the first and second surfaces of the dielectric elastomer material. Any suitable material capable of transmitting an electric current may be used as the first and second electrodes, although the materials used are preferably provided in a compliant form. Suitable materials that may be mentioned herein include, but are not limited to, carbon greases, one or more metal nanowires, hydrogels, ion gels, carbon nanotubes, liquid metals, and combinations thereof. Any suitable metal may be used in the metal nanowires, although in specific embodiments that may be mentioned herein, the metal nanowires may be formed of silver. As will be appreciated, the first and second electrodes may not need to be made of the same material. In this way, first and second electrodes made of different materials may be used accordingly.
[0116] As used herein, the term "liquid metal" is intended to refer to an elemental metal or metal alloy having a very low melting point that forms a eutectic that is liquid at room temperature. Examples of elemental metals that can be used as liquid metals include mercury, cesium, rubidium, francium, and gallium. It should be understood that in applications where the flexure actuator may be in close proximity to a person (or worn on a person's body), it is preferred to use metals that present less health risks. In this way, stable isotopes of radioactive metals can be used. When an alloy is used as the liquid metal, it can be any suitable alloy, such as a gallium indium tin alloy, the components of which are gallium, indium, and tin, in proportions suitable for forming a eutectic alloy at room temperature (e.g., 68wt% Ga, 22wt% In, and 10wt% Sn).
[0117] In embodiments of the present invention that may be mentioned herein, the first and second electrodes may be formed of silver nanowires.
[0118] As described above, the first and second electrodes sandwich a dielectric elastomer material film having a first surface and a second surface. Thus, the first electrode may be formed on the first surface of the film, and the second electrode may be formed on the second surface of the dielectric elastomer material film. For efficient operation, the placement of the first and second electrodes on the dielectric elastomer material film may be substantially identical, such that the degree of overlap is substantially complete, excluding manufacturing tolerances and any additional wiring that may be required to supply current to the electrodes.
[0119] In order to function properly, at least a portion of the first and second surfaces of the dielectric elastomer material film should not be covered by the first and second electrodes, respectively. In examples that may be mentioned herein, the first and second electrode areas may each occupy 5% to 50%, such as 10 to 40%, such as 15 to 30% of the area on the first and second surfaces of the dielectric elastomer material film, respectively.
[0120] For the avoidance of doubt, it is expressly contemplated that where multiple numerical ranges are cited herein relating to the same feature, it is intended that the endpoints of each range be combined in any order to provide further contemplated (and implicitly disclosed) ranges. Thus, with respect to the above related numerical ranges, the following areas are disclosed:
[0121] 5% to 10%, 5% to 15%, 5% to 30%, 5% to 40%, 5% to 50%;
[0122] 10% to 15%, 10% to 30%, 10% to 40%, 10% to 50%;
[0123] 15% to 30%, 15% to 40%, 15% to 50%;
[0124] 30% to 40%, 30% to 50%; and
[0125] 40% to 50%.
[0126] As described above, the flexure actuator requires the presence of a dielectric elastomeric material film. Dielectric elastomeric materials are a class of smart materials that can produce large strains (i.e., mechanical deformations) when subjected to external stimuli (i.e., application of an electric current). In addition, when the dielectric elastomeric material is subjected to such strains, it can also generate an electric current due to the strain. The dielectric elastomeric material film used in the aspects and embodiments of the present invention disclosed herein is formed by the random block copolymerization of a polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl end groups and a polar polymer material having two or more acrylate or vinyl end groups.
[0127] As used herein, "acrylate end groups" are intended to encompass any acrylate groups that can be feasibly used in such copolymerization reactions. Examples of suitable acrylate groups include unsubstituted acrylate groups themselves or alkyl derivatives thereof, such as methyl methacrylate, ethyl methacrylate, and the like.
[0128] Similarly, when used herein, "vinyl end group" is intended to encompass any vinyl group that can be feasibly used in such copolymerization reactions. Examples of suitable vinyl groups include vinyl groups themselves or alkyl derivatives thereof, such as methyl groups, ethyl groups, etc., without substituents at one or more unsubstituted positions of unsubstituted vinyl groups. Examples of suitable polymeric materials including silicon or nitrogen atoms having two or more vinyl end groups can be inferred from the polymeric materials including silicon or nitrogen atoms having two or more acrylate end groups disclosed herein.
[0129] In certain embodiments of the invention, acrylate end groups may be preferred.
[0130] The dielectric elastomer material film is formed by random block copolymerization of a polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups and a polar polymer material having two or more acrylate or vinyl end groups. As will be appreciated, the exact structure or structures of the resulting copolymer material will depend on the number of acrylate or vinyl end groups present. Without wishing to be bound by theory, in embodiments where both the polymer material comprising silicon or nitrogen atoms and the polar polymer material have two acrylate or vinyl end groups, it is believed that the resulting product may have one of a variety of structures selected from Formulas Ia, Ib, and Ic, wherein A represents a polymer material comprising silicon or nitrogen atoms and B represents a polar polymer material.
[0131]
[0132] Without wishing to be bound by theory, it is believed that the introduction of a polar polymer material (e.g., PEGDA) results in a significant change in the mechanical properties of one or more of the resulting copolymer materials. This may be due to an increase in the number of chemical crosslinks within the polymer matrix caused by the addition of the polar polymer material, which may act to anchor the polymer chains to each other, and thus minimize the lateral sliding of the polymer chains to each other. This is demonstrated by the significantly reduced viscoelastic properties of one or more of the resulting copolymer materials and the elongation at break properties when compared to materials containing only polymer materials including silicon or nitrogen atoms, which show a high elongation at break (see Example 2). Additional evidence is provided by the fact that the hysteresis losses during mechanical cyclic loading decrease with increasing concentrations of polar polymer materials (e.g., PEGDA) in the dielectric elastomeric material. This reduction in hysteresis losses indicates a reduction in energy dissipation of molecular motion. Further, the resulting copolymer material also has a higher dielectric constant than the dielectric constant of a polymer material that does not include a polar polymer material. As will be appreciated, when one or more such copolymer materials are incorporated into the buckling actuator of the present invention, the enhanced properties of the materials disclosed herein improve the performance of the actuator.
[0133] As will be appreciated, Formulas Ia to Ic are intended to illustrate possible structures that may be obtained by the reaction of the above-mentioned polymeric material comprising silicon or nitrogen atoms having two acrylate or vinyl end groups with a polar polymeric material having two acrylate or vinyl end groups. This is because the reaction between these materials will be random, and therefore the exact combination of components A and B (as defined above) cannot be predicted. Further, it will also be appreciated that one or more of these structures may be present in the reaction product, which may therefore be described as a mixture comprising one or more of the suggested structures of Formulas Ia to Ic.
[0134] Finally, it should be understood that when one or both of the polymer material including silicon or nitrogen atoms and / or the polar polymer material have three or more acrylate or vinyl end groups, the resulting copolymer or polymer network, mixture can be analogized from the above description of the case where there are two acrylate or vinyl end groups on each component.
[0135] As described below, urethane acrylate polymer materials (PUA) can be used as polymer materials including silicon or nitrogen atoms. Generally, any substitute for PUA used in a flexural dielectric elastomer actuator (DEA) should have a high fracture strain, and therefore a low elastic modulus. This ensures that the dielectric elastomer is easily deformed when an electric field is applied, allowing out-of-plane displacement to occur. However, in order to reduce the tendency of electromechanical instability, the modulus should not be too low. Thus, the elastic modulus can be, for example, between 0.1 and 4 MPa, such as 0.3 to 4 MPa.
[0136] Any suitable polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups may be used in embodiments of the present invention. Examples of suitable polymer materials comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups include, but are not limited to, urethane acrylate polymer materials having two or more acrylate end groups, poly(dimethylsiloxane) dimethacrylate, and thermoplastic polyurethanes having two or more acrylate end groups.
[0137] Suitable polymeric materials including silicon or nitrogen atoms having two or more acrylate or vinyl end groups may be materials having a number average molecular weight greater than 20,000 Daltons (e.g., 20,001 to 50,000 Daltons). Without wishing to be bound by theory, it is believed that if the number average molecular weight is less than 20,000, a film will not be formed and the resulting material will be too hard. In addition, suitable polymeric materials including silicon or nitrogen atoms having two or more acrylate or vinyl end groups may be materials having an elongation at break greater than or equal to 200% (details on how to measure the elongation at break are provided in the Examples section below).
[0138] In embodiments of the invention that may be described herein, one or both of the polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl end groups and the polar polymer material having two or more acrylate or vinyl end groups may have two acrylate end groups.
[0139] Any suitable urethane acrylate polymer material with two acrylate end groups can be used in embodiments of the present invention. Examples of such suitable materials include, but are not limited to, aliphatic acrylate polymer materials with two acrylate end groups. Examples of aliphatic acrylate polymer materials with two acrylate end groups include, but are not limited to: CN310, CN8881, CN8884, CN8888, CN9004, CN9014, CN9028, CN9031, CN9002, CN966J75, CN9018, CN9021, CN3108, CN3211, CN8004 and combinations thereof. In a specific embodiment of the present invention that may be mentioned herein, the urethane acrylate polymer material with two acrylate end groups may be CN9021.
[0140] As will be appreciated, the names provided above are trade names for aliphatic acrylate polymer materials having two acrylate end groups. However, while these materials are believed to have a common structure, represented by Formula II below, the exact composition of these materials is retained by the manufacturer as a trade secret.
[0141]
[0142] In the above formula II, -[O-R1] n The -group may be selected from a polyol or a polyacrylate. When used herein, "n" is provided to indicate that this is a repeating unit. Since many aliphatic acrylate polymer materials that can be used herein are commercial materials, the exact structure of which is known only to the manufacturer of the compound, a specific numerical range for n is not explicitly stated herein.
[0143] Examples of suitable polyols that can be used in the above materials include, but are not limited to, polyethylene glycol and poly(propylene glycol). Examples of suitable polyacrylates that can be used in the above materials include, but are not limited to, poly(2-hydroxyethyl methacrylate), poly(2-hydroxyethyl acrylate), and poly(2-hydroxybutyl acrylate). As will be understood, the terms "polyol" and "polyacrylate" are used herein to refer to polymeric materials that form part of the aliphatic acrylate polymer materials disclosed herein. For the avoidance of doubt, the term "polyol" may be used herein to refer to polyethers, such as polyethylene glycol.
[0144] The R2 group in the above formula II can be selected from isocyanates. Examples of suitable isocyanates that can be used in the above materials include, but are not limited to, hexamethylene diisocyanate (HDI), isophorone diisocyanate (IDI), bis(4-isocyanatocyclohexyl)methane (HDI), 12 MDI) and 4,4'-methylenebis(phenyl isocyanate) (MDI).
[0145] As used herein, the term "polar polymer material" may be intended herein to refer to a material having a number average molecular weight of 200 to 1,000 Daltons (e.g., 250 to 750 Daltons, such as 400 to 600 Daltons, such as 575 Daltons). The polar polymer material has a polymer structure that will tend to align with the field direction of the alternating electric field. In addition or alternatively, as used herein, the term "polar polymer material" may refer to a material having a dielectric constant higher than a polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl end groups. The elongation at break of the polar polymer material may be 0-150% (details on how to measure the elongation at break are provided in the Examples section below). As should be understood, some of the polar polymer materials listed here may not be able to form a film due to their low molecular weight, meaning that the elongation at break of these materials is actually 0%.
[0146] Without wishing to be bound by theory, selection of a polar polymeric material having a number average molecular weight in the range of 200 to 1,000 Daltons can allow the material to act as a crosslinker in the dielectric elastomeric materials described herein. Additionally, without wishing to be bound by theory, it is believed that polar polymeric materials such as poly(ethylene glycol) diacrylate (PEGDA) can have a relatively high density of polar groups for their molecular weight compared to polymeric materials including silicon or nitrogen atoms.
[0147] For the avoidance of doubt, the polar polymeric materials mentioned herein do not contain silicon.In specific embodiments that may be mentioned herein, the polar polymeric materials mentioned herein do not contain silicon and / or nitrogen atoms.
[0148] The polar polymer materials used herein can provide crosslinks with the resulting dielectric elastomeric material. Although the presence of these chemical crosslinks increases the elastic modulus of the dielectric elastomeric material, the introduction of additional polar groups present in the polar polymer material enhances the dielectric constant of the dielectric elastomeric material, offsetting its effects on actuation properties, such as maximum area strain and work density.
[0149] In the embodiments described below, poly(ethylene glycol) diacrylate (PEGDA) is used as the polar polymer material in combination with CN9021. In these embodiments, as the concentration of PEGDA increases, the observed elastic modulus also increases, resulting in suppression of electromechanical instability. This provides a key distinction between using PEGDA (and similar polymer molecules) and small cross-linking molecules such as 1,6-hexanediol diacrylate (HDDA). When comparing the chemical structures of HDDA and PEGDA (the structure of PEGDA is shown in FIG. Figure 1 b), it can be observed that there are significantly more polar groups (CO) in PEGDA compared to HDDA, resulting in an overall increase in the dielectric constant. This highlights that polar polymer molecules that can act as polar crosslinkers need to contain repeating units with polar groups.
[0150] Substitutes for PEGDA should contain enough polar groups so that the dielectric permittivity of the resulting polymer is increased. In addition, these polar compounds should be di(or more) functional groups that can react so that they can act as polar crosslinkers to anchor polymer chains to adjust viscoelasticity. Examples of such groups are provided below.
[0151] Any suitable polar polymer material with two or more acrylate or vinyl end groups can be used. For example, the polar polymer material with two or more acrylate or vinyl end groups can be selected from a list including but not limited to: poly (trimethylolpropane triacrylate-co-ethylene dimethacrylate), poly (ethylene glycol) diacrylate (PEGDA), poly (caprolactone) dimethacrylate, poly (propylene glycol) dimethacrylate and combinations thereof. In a specific embodiment that may be mentioned herein, the polar polymer material with two or more acrylate or vinyl end groups can be poly (ethylene glycol) diacrylate (PEGDA). As described above, the polar polymer material with two or more acrylate or vinyl end groups can have two acrylate end groups.
[0152] Any suitable molecular weight of the polar polymer material having two or more acrylate or vinyl end groups can be used to form the dielectric elastomeric material. For example, the polar polymer material having two or more acrylate or vinyl end groups can have a number average molecular weight of 200 to 1,000 Daltons, such as 250 to 750 Daltons, such as 400 to 600 Daltons, such as 575 Daltons.
[0153] Any suitable amount of a polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl end groups and a polar polymer material having two or more acrylate or vinyl end groups may be used in the dielectric elastomer material herein. In an embodiment of the present invention, the polar polymer material having two or more acrylate or vinyl end groups may be present in the dielectric elastomer material in an amount of 5 to 15 wt %, such as 10 to 15 wt %. The balance of the dielectric elastomer material may be a polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl end groups, and the residue of any initiator used in the reaction for forming the dielectric elastomer material.
[0154] The dielectric elastomeric material formed by the reaction of a polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl end groups and a polar polymer material having two or more acrylate or vinyl end groups may have one or more of the following:
[0155] (Ai) Dielectric constant (ε r ) is greater than 3, such as 3.1 to 100, such as 5.8 to 20, such as 6 to 15, such as 6.2 to 9.4;
[0156] (Aii) an elastic modulus of 0.1 to 4 MPa, such as 0.3 to 4 MPa;
[0157] (Aiii) a dielectric breakdown less than or equal to 30 V / μm, such as 10 V / μm to 25 V / μm, such as 8 V / μm to 25 V / μm, such as 10 V / μm to 20 V / μm; and
[0158] (Aiv) Elongation at break greater than 50%, such as 50 to 960%, such as 50 to 500%, such as 150 to 450%, such as 423%.
[0159] The experimental section below provides details on how these properties were measured.
[0160] Dielectric breakdown can be determined under an electric field (for a particular material) where there is a current surge exceeding 0.01 mA during the actuation measurement. Elongation at break can be determined by tensile testing as described in the Examples section below.
[0161] The resulting buckling actuator may have a displacement less than or equal to 1,250 μm, such as 100 to 1,250 μm, such as 500 to 1,250 μm, such as 250 to 750 μm, such as 1,000 to 1,250 μm, when a voltage is supplied to the first and second electrodes. The experimental section below provides details on how to measure this property. More specifically, a displacement of 100 to 1,250 μm may refer to static feedback, while for dynamic feedback, the displacement may be about 0.1 μm (e.g., 0.01 to 10 μm, such as 0.05 to 1 μm).
[0162] As used herein, the term "dynamic displacement" refers to displacement achieved by applying an alternating current (AC) electric field, where a buckling actuator can rapidly change form due to the fluctuating electric field. In contrast, as used herein, "static displacement" refers to displacement produced by a direct current (DC) electric field, where the actuator will buckle and not return to its original state until the electric field is removed.
[0163] Without wishing to be bound by theory, buckling (or out-of-plane deflection) is generally caused by compressive stresses generated along the entire actuator during application of voltage. Figure 8 As shown in Figure 1, this causes a conflict between the expansion of the electro-active area (the area with overlapping electrodes) and the electro-passive area (the area without electrodes). When a voltage is applied to the electrodes, the electro-active area will try to expand. However, since no voltage is applied to the electro-passive area, it will remain stagnant or "fixed". In this way, the electro-passive area thus opposes the expansion of the electro-active area and generates compressive stresses that cause buckling.
[0164] For stable out-of-plane actuation, the area of the active region (overlapping electrodes) should be at most 50% of the entire area of the dielectric elastomer. For example, the first and second electrode areas may each occupy 5% to 50%, such as 10 to 40%, such as 15 to 30% of the area on the first and second surfaces of the dielectric elastomer material film, respectively. This ensures that the inactive region provides sufficient compressive stress to cause out-of-plane actuation.
[0165] As will be appreciated, an advantage associated with the presently described buckling actuator systems is that they do not need to include any rigid boundaries or any framework (rigid or otherwise) to induce compressive stresses. Thus, the buckling actuators described herein may also be placed on a flexible substrate (e.g., as in Examples 6 and Fig.18 a) to provide flexibility. In such an embodiment, the second electrode can be placed on the flexible substrate, and the dielectric elastomer material film is formed on top of the flexible substrate and at least a portion of the second electrode. As will be appreciated, since the terms "first" and "second" as described herein are essentially arbitrary, the opposite arrangement is correct. Such materials also allow the development of fully flexible actuators that can operate even in a bent state.
[0166] In yet other embodiments, a flexible substrate may also be attached to both the first and second surfaces of the buckling actuator if this is desired.
[0167] As described above, the buckling actuators disclosed herein do not need to include any kind of rigid constraining member. Thus, when a voltage is applied, the buckling actuators described herein are capable of out-of-plane actuation in the absence of a rigid constraining member.
[0168] Considering the types of materials used to make the buckling actuators described herein, an additional advantage associated with these devices is that they can be transparent. In other words, the dielectric elastomer material, the first and second electrodes, and (when present) any flexible substrate(s) can all be selected to be transparent.
[0169] Furthermore, the use of dielectric elastomer materials in the buckling actuator allows the actuator to achieve superior performance compared to the use of materials containing only polymer materials including silicon or nitrogen atoms. These improved properties include stable and greater actuation with minimal drift and faster response and recovery times, which are described in the embodiments below. Further, the pull-in instability of the actuator is suppressed, thereby allowing for greater out-of-plane displacement heights (i.e., up to 1.5-2.0 mm, see Fig.14 a and 21b) have enhanced actuation performance, which is greater than the minimum skin deformation required for detection in tactile devices.
[0170] As will be appreciated, applications of the flexure actuators disclosed herein may involve a single flexure actuator used alone, a plurality of flexure actuators used in complete isolation from one another, or a plurality of flexure actuators used in an array. Thus, an array of flexure actuators comprising a plurality of flexure actuators is also disclosed herein. An example of such an array of flexure actuators is an array in which the flexure actuators are arranged in a cross-knot configuration. Further details of this arrangement are described in the Examples section below. As will be appreciated, any suitable array of flexure actuators may be used. As used herein, the term "array of actuators" is intended to refer to a plurality of actuators electrically connected together such that more than one of the plurality of actuators can be activated by a single power source at any one time.
[0171] In another aspect of the present invention, there is also disclosed a dielectric elastomeric material formed by random block copolymerization of:
[0172] a polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups; and
[0173] A polar polymeric material having two or more acrylate or vinyl terminal groups.
[0174] As should be appreciated, the dielectric elastomer material disclosed in this aspect is the same as the dielectric elastomer material disclosed above as part of the buckling actuator, and therefore, the variations described above with respect to the dielectric elastomer material also apply here and will not be repeated.
[0175] The above dielectric elastomer material can be formed by any suitable method. A specific method that can be used herein includes the following steps:
[0176] (i) providing a mixture comprising a polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups and a polar polymer material having two or more acrylate or vinyl end groups in the presence of a free radical initiator and optionally in the presence of a solvent; and
[0177] (ii) reacting the mixture at an elevated temperature for a period of time to provide the dielectric elastomeric material.
[0178] Although the reaction itself does not require a solvent, it may be useful to include a solvent when attempting to make thin films of 200 μm or less, as the viscosity of the materials used may otherwise make this challenging to achieve. As will be appreciated, the mixture (along with the solvent) may be cast onto a petri dish (or other container) and the solvent allowed to evaporate leaving the desired film. Additionally or alternatively, a solvent may be added (if desired) to help control the viscosity of the mixture in order to facilitate printing of the dielectric elastomer material.
[0179] Since the polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups and the polar polymer material having two or more acrylate or vinyl end groups have been described in detail above, they will not be described again here. For the avoidance of doubt, the description provided above for the polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups and the polar polymer material having two or more acrylate or vinyl end groups is applicable to these components in the method of forming a dielectric elastomer material.
[0180] As will be appreciated, since the dielectric elastomeric material described herein may find application in a buckling actuator as described herein, the dielectric elastomeric material may be provided in the form of a film after completing step (ii) above.
[0181] In an embodiment of the above method, the solvent and the polymeric material including silicon or nitrogen atoms having two or more acrylate or vinyl end groups may have a weight to weight ratio of 10:1 to 1:1, such as 3:1 to 1:1. As will be appreciated, any suitable solvent compatible with the reaction conditions may be used. Suitable solvents include, but are not limited to, acetone and / or isopropanol.
[0182] The reaction in the above step (ii) involves an elevated temperature - a temperature that is higher than the normal ambient temperature of the environment in which the reaction occurs. Any suitable elevated temperature can be used. Examples of suitable elevated temperatures include, but are not limited to, 50 to 100 ° C, such as 70 to 90 ° C. As will be appreciated, the reaction temperature can be limited to the boiling temperature of any solvent present, which will then be affected by the amount of a polymer material including silicon or nitrogen atoms and a polar polymer material with two or more acrylates or vinyl end groups present therein. In an embodiment where the solvent reaches its boiling temperature, the reaction can be run under reflux conditions so that the evaporated solvent is condensed and returned to the reaction mixture.
[0183] The reaction in step (ii) above can be run for any suitable period of time to provide the desired dielectric elastomer material. Examples of suitable time periods include, but are not limited to, a period of 10 minutes to 24 hours, such as 15 minutes to 12 hours, such as 20 minutes to 1 hour, such as 30 minutes.
[0184] As described above, the reaction mixture used in step (i) of the method for making a dielectric elastomeric material requires the presence of a free radical initiator. Any suitable free radical initiator used with acrylate groups (including alkyl acrylate groups as defined herein) and / or vinyl groups can be used in the method. Any suitable amount of free radical initiator can be used. For example, the free radical initiator is present in an amount of at least 1 wt % of the mixture (e.g., 1 wt % to 10 wt %, such as 1 wt % to 5 wt %). When used herein, the term "mixture" is intended to refer to all components except any solvent (if present).
[0185] As will be appreciated, the buckling actuators disclosed herein may be applied to any application where their use may be valuable. These include, but are not limited to, training systems (such as for medicine, aerospace, and defense), gaming, robotics, and Braille readers, as well as high-precision applications such as tunable lenses and gratings.
[0186] As described herein, the dielectric elastomeric materials described herein are capable of achieving a maximum strain area that is significantly higher than the maximum strain area achievable by low viscoelastic materials (such as silicone) that also require higher operating voltages. In addition, as described above, the flexure actuators disclosed herein do not need to include rigid components, which are typically used to achieve a pre-stretched state to reduce viscoelastic effects and improve actuation performance. By not requiring rigid components to function, the disclosed flexure actuators are more easily integrated into soft and flexible bodies, which can make them more easily usable in the formation of wearable devices.
[0187] Further aspects and embodiments of the invention will now be described by reference to the following examples.
[0188] Example
[0189] Material
[0190] CN9021, an aliphatic polyurethane acrylate (PUA) developed for lamination and pressure-sensitive adhesives, was purchased from Sartomer and used as received. CN9021 is said to have: a viscosity (at 60°C) of 1500-3500 cps; an elastic modulus of 0.827 MPa; and a glass transition temperature of -54°C. It has an average M nPolyethylene glycol diacrylate (PEGDA) with 575 and 2000, and azobisisobutyronitrile (AIBN) were obtained from Sigma Aldrich and used as received. Carbon grease was purchased from Nanjing Xilite Adhesive Co., Ltd. and used as received. Silver nanowires with an average diameter of 50 nm and a length of 100-200 μm were purchased from XFANO. The silver nanowires were dispersed in isopropanol at a concentration of 0.5 mg / mL.
[0191] General Method 1 - Performance Characterization of Dielectric Elastomer Actuators (DEAs)
[0192] The vertical deflection from the center of the electrode was determined using an Epsilon optoNCDT laser displacement sensor. For static actuation experiments, the voltage was increased by 0.5 kV every 10 seconds. The actuation strain was determined by calculating the change in electrode area based on geometric relationships. TM A Model PD05034 high voltage AC power amplifier was used to amplify the signal from the pulse generator for cyclic actuation measurements. Unless otherwise specified, 10 kV μm at 0.5 Hz was used. -1 To evaluate the response time, a 10 kV μm -1 The response time of the actuator is quantified by the time it takes to reach 90% of the maximum displacement per cycle. 0.9 For each copolymer formulation, three samples were tested.
[0193] Example 1. Synthesis and characterization of PUA-PEGDA copolymer films containing various amounts of PEGDA
[0194] The PUA-PEGDA copolymer film used to manufacture the dielectric elastomer actuator of the present invention was synthesized using polyurethane acrylate (PUA, CN9021) and polyethylene glycol diacrylate (PEGDA) by free radical polymerization (or random block copolymerization).
[0195] Experimental – Synthesis and Characterization
[0196] The following describes a typical synthesis sequence of PUA-PEGDA copolymer membranes. PUA (CN9021) was mixed with different concentrations of PEGDA (5, 10 and 15 wt %, M n=575) was mixed, and 1wt% of AIBN was added to the mixture and mixed thoroughly. The resulting mixture was degassed for 1hr to remove air bubbles that may form defects in the manufactured film. The resulting degassed mixture was then cured on an electric furnace at 90°C for 1-2hr under an inert environment to allow free radical polymerization. The as-synthesized polymer film was carefully peeled off, and an average film thickness of 0.43mm was obtained. The original PUA (CN9021) film was synthesized by the same polymerization reaction, but without adding PEGDA. The original PUA film is represented as PUA, and the copolymer film is represented as PUA-PEGDA-X, where X represents the weight percentage of PEGDA.
[0197] Typically, no solvent is required to carry out the reaction or prepare the copolymer film of the present invention. However, the high viscosity of the CN9021 polymer material makes it difficult to make thin films <200 μm. Therefore, thinner films <200 μm can be made by adding acetone to the CN9021 resin in a 1:1 weight ratio.
[0198] When the mixture (along with the solvent) is cast onto a petri dish, the solvent evaporates, leaving behind a thin film.
[0199] Fourier transform infrared (FTIR-ATR, Perkin Elmer, Frontier) spectroscopy was used to analyze the -1 FTIR spectra were measured by scanning each film 32 times at a resolution of 1.5 Å. The as-synthesized PUA-PEGDA was measured on a 400 MHz Bruker DPX 400 NMR spectrometer in deuterated chloroform at room temperature. 1 H nuclear magnetic resonance (NMR) spectroscopy. Chemical shifts are reported as delta values (ppm) relative to the residual chloroform peak.
[0200] Results and Discussion
[0201] Polyurethane acrylate (PUA) type CN9021 and low molecular weight PEGDA (M n = 575) using free radical polymerization (for the molecular structures of PUA and PEGDA, see Figure 1 a and b).
[0202] Typically, in the first step (initiation), the AIBN free radical initiator is activated at 90°C to form free radicals, which react with monomers of PEGDA or PUA (CN9021) through addition reactions. In the propagation step, the polymer chain grows by sequentially adding PEGDA or PUA monomers to form macroradicals. Finally, in the termination step, the polymer macroradicals combine together to form a random block copolymer composed of PUA and PEGDA monomers. The feasibility of this polymerization mechanism mode can be attributed to the presence of carbon double bonds in PEGDA and PUA, which allows them to undergo addition reactions.
[0203] In order to verify the successful copolymerization between the two compounds, FTIR ( Figure 2 a and b, respectively for the initial and subsequent batches of PUA-PEGDA) and NMR spectra characterizing the as-synthesized polymer. FTIR measurements of the as-synthesized pristine PUA film showed a strong kinetic energy at 2750-3100 cm -1 The absorption peak of CH2 in the region (–CH stretching consists of asymmetric –CH3 stretching, asymmetric –CH2 stretching, symmetric –CH3 stretching and symmetric –CH2 stretching) is at 1457 cm -1 H–C–H shear bending at 810 cm -1 =CH stretching at 3350-3200 cm -1 -NH- stretching vibration at 1720-1727cm -1 The C=O stretching vibration at 1520-1580cm -1 The –NH– stretching vibration at 1635 cm-1 confirmed the cross-linking between PEGDA and PUA via free radical polymerization. -1 ) peak shift indicates that cross-linking (i.e., more rigid C=O bonds) has occurred. In addition, a peak shift at 1635 cm -1 The peak corresponding to C=C stretching is at , thus indicating that some C=C bonds remain unreacted.With the successful copolymerization of PUA and PEGDA, a chemical cross-linking network is established between the polymer chains, thus preventing the chains from sliding laterally with respect to each other.
[0204] Table 1. Characteristic FT-IR peaks of as-synthesized PUA-PEGDA copolymers
[0205]
[0206] Furthermore, the PUA-PEGDA copolymer 1The H NMR spectrum showed peaks (acrylate) at 5.76–5.86, 6.08–6.18, and 6.41–6.47 ppm, which confirmed the presence of acrylate groups in the PUA-PEGDA copolymer structure. Important characteristic signals of carbamate groups (–NH–(C=O)–O–) in the PUA-PEGDA copolymer sample were also observed in the region of 7.21–7.29 ppm, indicating the presence of carbamate groups in the PUA-PEGDA structure.
[0207] Example 2. Dielectric and Mechanical Properties of As-synthesized PUA-PEGDA Copolymer Films with Various Amounts of PEGDA
[0208] The dielectric and mechanical properties of the as-synthesized PUA-PEGDA of Example 1 were studied to investigate the effect of incorporating various amounts of PEGDA into the copolymer films.
[0209] experiment
[0210] Characterization of dielectric properties
[0211] Dielectric constant measurements were performed using an Agilent E4980a LCR meter over a frequency range of 1kHz to 1MHz. A 1V AC signal was applied to the sample, and the dielectric constant was calculated from the measured capacitance using the following relationship: C = (ε0εΑ) / d, where A is defined as the overlap area between the top and bottom electrodes, ε0 is the vacuum permittivity, C is the measured capacitance, and d is the polymer film thickness. The elastomer sample was placed between the two electrodes for measurement.
[0212] Characterization of mechanical properties
[0213] According to ASTM D638-14, the V-type tensile test specimens were prepared. The tensile strength was 3.33 mm s on an Instron 5567 universal testing machine. -1 The tensile test was performed at a strain rate of 1.0 or 3.33 mm s -1 The strain rate was 10-30 cycles with an ultimate strain of 50% (for the initial batch) or 100% (for subsequent batches). To obtain the elastic modulus, the gradient of the linear region of the stress-strain curve was measured at ±5% of the respective strain. The mechanical properties of the polymer film as synthesized are shown in Table 2.
[0214] Table 2. Comparison of mechanical properties of as-synthesized polymer films.
[0215]
[0216] a Apparent modulus at 10% strain calculated from the stress-strain curve.
[0217] b The apparent modulus at 50% strain calculated from the stress-strain curve.
[0218] Results and Discussion
[0219] Dielectric properties of PUA-PEGDA copolymer films
[0220] For the initial batch of PUA-PEGDA copolymers, it was observed that the addition of PEGDA resulted in an improvement in the dielectric constant of the as-synthesized PUA-PEGDA copolymers ( Figure 3 a). The dielectric permittivity of subsequent batches of copolymer films with various concentrations of PEGDA was also studied. Similar to the initial batch, a dramatic improvement in permittivity was observed with increasing PEGDA concentration ( Figure 3 b). The dielectric constant increases from 5.52 to 8.87 at 1kHz ( Figure 3 b), while the commercial VHB 4905 (for comparison) has a measured permittivity of 4.4 at 1 kHz. This improvement can be attributed to the increase in the polarity of the copolymer film, due to the increase in the number of polar CO and C=O groups with increasing PEGDA content. This finding suggests that the dielectric properties of the film can be tuned by controlling the concentration of PEGDA. This is important because the dielectric permittivity is proportional to the generated Maxwell pressure, and therefore, an increase in the dielectric constant can help improve the performance of the dielectric elastomer actuator due to the increase in Maxwell pressure.
[0221] As the frequency increases, the permittivity of the copolymer decreases, for the initial and subsequent batches, respectively. Figure 4 This phenomenon is generally associated with dielectric relaxation, where the polar groups on the polymer chain are unable to keep up with the alternating current, resulting in a loss of contribution to the dielectric permittivity.
[0222] Mechanical properties of PUA-PEGDA copolymer films
[0223] The effect of chemical crosslinking between PEGDA and pristine PUA on the mechanical properties can be respectively Figure 5 The stress-strain curves of the initial and subsequent batches of copolymer films in a and b are observed. Figure 5 An increase in the elastic modulus of the initial batch of copolymer films is observed in the stress-strain curve in a. As the cross-linking density increases, the number of defects such as microvoids and cracks may decrease, thus improving the dielectric breakdown strength of the polymer.
[0224] Subsequent batches of PUA-PEGDA copolymer films with concentrations up to 10 wt% PEGDA exhibited nonlinear behavior with a slow gradual increase in stress at low strains due to the unfolding of the polymer chains ( Figure 5b) However, at larger strains, as the polymer chains begin to become taut and aligned, the elastomer exhibits strain hardening behavior, where the elastic modulus increases rapidly.
[0225] At 15wt% PEGDA, nonlinear elastomeric behavior is weakened due to increased crosslinking, accompanied by a decrease in the maximum achievable elongation. This phenomenon is accompanied by a decrease in the apparent modulus, which can be attributed to the increase in the length between crosslinks when the probability of the PEGDA acrylate groups to react with each other at higher concentrations increases. As the number of chemical crosslinks between the PEGDA and PUA polymer chains increases, the mobility of the chains is severely restricted, which reduces the maximum elongation of the original PUA from 960% elongation to 167%. Note that the maximum elongation at 15wt% PEGDA is comparable to the maximum elongation of polydimethylsiloxane (PDMS) (Sylgard 184) by Dow Corning. A summary of the mechanical properties of the manufactured films is provided in Table 2 above.
[0226] Loading and unloading cycle tests performed on the initial batch of copolymer films showed hysteresis behavior of the films, which supports the decrease in viscoelastic properties of the films with increasing PEGDA concentration ( Figure 6 ad). These hysteresis curves are the result of tensile tests performed on polymer films loaded and unloaded at a strain rate of 3.33 mm / s and a limiting strain of 50%. Figure 6 The decrease in hysteresis loss with increasing PEGDA concentration shown in ad may be related to the decrease in the viscoelastic behavior of the film due to chemical cross-linking.
[0227] Subsequent batches of copolymer films were subjected to loading-unloading cycle tests (at 1 mm s -1 The viscoelastic behavior of the manufactured copolymers was evaluated at a strain rate of 1000 μg / min for 30 cycles. Similar to the initial batch, the subsequent batches exhibited hysteresis losses, which are represented by the area enclosed in the curve ( Figure 7 ad). This area represents the energy dissipated during the cycle, which is related to the internal friction and sliding of the polymer chains in the viscoelastic elastomer. As a result of the Mullins effect, large hysteresis losses were observed during the first cycle for all samples, with the largest losses exhibited by the original PUA sample. After the second cycle, the stress-softening behavior during cyclic loading began to reach a steady state, where a stable hysteresis loop was formed.
[0228] As the PEGDA concentration increases, a decrease in hysteresis losses after the first cycle is observed. This is most likely due to an increase in the cross-link density between polymer chains, which restricts motion and reduces dissipated energy. Furthermore, a decrease in hysteresis implies reduced viscoelastic losses, which can be correlated with the cyclic testing up to 1050 cycles ( Fig.17 ah) is related to the improved electromechanical stability.
[0229] This phenomenon contributes to the enhanced dynamic response time of the dielectric elastomer actuator, which is discussed in Example 5.
[0230] Example 3. Fabrication of the Dielectric Elastomer Actuator (DEA) of the Present Invention Using Carbon Grease as Electrode
[0231] The as-synthesized PUA-PEGDA copolymer film of Example 1 was used to fabricate the buckled dielectric elastomeric actuator (DEA) of the present invention.
[0232] like Figure 8 As shown in a and b, DEA (10) includes a layer of PUA-PEGDA copolymer film (15), and conductive electrodes (20) are coated on each top and bottom surface of the film (15). The electrodes (20) are positioned on the film (15) so that they overlap each other. The area covered by the electrodes (20) on the film (15) is an electrically active area, while the area not covered by the electrodes is an electrically passive area. In addition, a conductive tape (25) can be applied to the film (15) to extend the electrodes (20) to the periphery of the film (15). Such a conductive tape (25) provides a conductive point for a current source further away from the electrodes and closer to the periphery of the film (15). This allows the current source to be applied away from the electrodes to minimize damage to the DEA. Such a conductive tape (25) can have the same material as the electrodes. For experimental purposes, a glass substrate (30) with a window is used to support the DEA. If desired, the substrate (30) can be replaced with any other material (e.g., cloth, polyethylene terephthalate (PET) or any plastic substrate) to provide flexibility. The operation of the DEA has little dependence on the substrate used, as it can employ a wide range of substrates, such as cloth, PET or even glass. However, it should be understood that the DEA can also function without the substrate (30). The use of the substrate is only to support the DEA for experimental measurements. A cross-sectional view and a photograph of the DEA are shown in FIG. Figure 8 c and d.
[0233] Typically, the as-synthesized PUA-PEGDA copolymer membranes (PUA, PUA-PEGDA-5, PUA-PEGDA-10 or PUA-PEGDA-15) of Example 1 with an average thickness of 0.43 mm were placed on an internal glass holder prepared with a 2 cm x 2 cm hole to allow out-of-plane actuation. Carbon grease was used as electrodes, which was coated on a circular area with a diameter of 3 mm on the top and bottom surfaces of the membrane. Copper tape was used to provide electrical connections to a Unicorn UHP-75 high voltage DC power supply.
[0234] Example 4. Static properties and temperature stability of as-prepared DEA
[0235] The static properties and temperature stability of the as-fabricated DEA of Example 3 were evaluated to understand the effect of including various amounts of PEGDA on DEA in the PUA-PEGDA copolymer films.
[0236] experiment
[0237] The static properties of as-manufactured DEA were evaluated as described in General Method 1.
[0238] To determine the temperature stability of DEA, the samples were stirred at 3 °C min in a liquid N2 environment. -1 Dynamic mechanical analysis (DMA) was performed in the temperature range of -40°C to 100°C with a heating rate of 1.5 %. DMA was performed according to ASTM D5026 with a dynamic mechanical analyzer (DMA, TA Instrument 329Q800) in the tensile mode under multi-frequency conditions.
[0239] The area strain is derived from the difference in the electrode area before and after actuation. The geometric relationship is taken into account by assuming that the electrode area forms a perfect dome during actuation (Carpi, F., et al., Smart Mater. Struct. 2015, 24, 105025). In this way, the area strain can be calculated as follows:
[0240]
[0241] where h o is the initial height, r o is the initial radius of the electrode, h is the height of the elevation, and r is the radius of the dome formed after voltage application. In this study, no air bias was applied to start the actuator from an elevated height (Ren, Z., et al., Macromolecules 2015, 49, 134-140). Thus, the initial height of the DEA was assumed to be zero.
[0242] In addition to using area strain to determine the performance of DEA, deflection strain (also called deflection to thickness ratio) was also characterized based on studies on similar device configurations (Renard, C., et al., Appl. Polym. Sci. 2017, 134, 45123; Chen, T., et al., Soft Mater. 2015, 13, 210-218).
[0243] Results and Discussion
[0244] To demonstrate a fully flexible device, a buckling mode actuator was set up without any elastomeric membrane pre-stretching. Carbon grease was coated on both surfaces with a circular overlapping area, which was defined as the electrically active area.
[0245] Typically, membrane buckling occurs when the electrically active region expands against the passive region of the DEA without overlapping electrodes. This phenomenon creates a boundary condition that inhibits lateral expansion of the electrically active region and generates compressive stresses across the DEA. When the buckling limit is exceeded, out-of-plane deflection is achieved as the membrane buckles. The actuated out-of-plane displacement ( Fig. 9 a and b).
[0246] Determine the area strain from the change in the electrically active area according to the geometric relationship ( Fig. 9 c, 10a-d), while the deflection strain is determined based on the deflection-to-thickness ratio ( Fig.11 ).like Fig. 9 c and Fig.10 As shown in a, pristine PUA exhibits a sudden increase in area strain before dielectric breakdown, which is not observed in PUA-PEGDA-5, -10, and -15 copolymers ( Fig.10 This finding is attributed to the nonlinear behavior of PUA, where its modulus becomes significantly smaller than that of PUA-PEGDA copolymers above 10% strain ( Figure 5 a). In the absence of applied pre-strain to prevent electromechanical instability, early breakdown of the PUA is expected.
[0247] In contrast, copolymers with higher concentrations of PEGDA (10 wt% and 15 wt%) showed resistance that exceeded the breakdown strength of pristine PUA and PUA-PEGDA-5 ( Fig.10 c and d). This is due to the increased stiffness from chemical crosslinking, which reduces the possibility of electromechanical instability. Under this influence, PUA-PEGDA-10 and PUA-PEGDA-15 were tested at higher electric field strengths to achieve higher maximum strains than PUA or PUA-PEGDA-5. A comparison between the area strains of DEA materials without pre-strain is presented in Table 3 below. Compared with low viscoelastic materials (such as silicone), PUA-PEGDA-15 exhibits higher area strains at lower electric field strengths without pre-stretching. This finding can be attributed to the high dielectric permittivity, which leads to a higher generated Maxwell pressure. It was also observed that the flexural strains of PUA and PUA-PEGDA copolymers follow a similar trend of area strain.
[0248] Table 3. Comparison of area strain between various DEA materials without pre-strain.
[0249]
[0250] a.Zhang,YY,et al.,Polym.Compos.2019,40,E62-E68.
[0251] b.Zhang,L.,et al.,J.Mater.Chem.C 2015,3,4883-4889.
[0252] c.Sun,H.,et al.,Polym.Chem.2019,10,633-645.
[0253] d.Zhao,Y.,et al.,Polymer 2018,137,269-275.
[0254] e. Shankar, R., et al., Macromol. Rapid Commun. 2007, 28, 1142-1147.
[0255] f.Renard,C.,et al.,RSC Adv.2017,7,22900-22908.
[0256] g.Xiang,D.,et al.,RSC Adv.2017,7,55610-55619.
[0257] Under the isochoric assumption, the work density of the material (u e ) is calculated as the work done by the actuator divided by its volume (as shown in Equation 2 below), where P represents the generated Maxwell pressure, and s z is the thickness strain determined from the measured area strain (Ha, SM, et al. Proc. SPIE, 2008, 6927, 69272C).
[0258]
[0259] like Fig. 9 As shown in Figure d, as the PEGDA concentration increases, the decrease in work density caused by increased cross-linking gradually minimizes. -1 At an electric field strength of 1.5 Å, the work density of PUA-PEGDA-15 is similar to that of the original PUA sample, indicating an optimal balance between the effects of the increased dielectric constant and elastic modulus. Furthermore, when PUA-PEGDA-15 can be tested at higher electric field strengths, the maximum work density achieved by PUA-PEGDA-15 is the highest among the measured samples. Thus, this clearly shows the effectiveness of polar crosslinking in increasing the load that the actuator can drive.
[0260] To illustrate the temperature-dependent behavior of DEA, the temperature-dependent electromechanical susceptibility ( Fig.12 ). Here, electrochemical sensitivity (or stability) is defined as the ratio between the dielectric constant and the storage modulus at 1 kHz (Zhao, H., et al., Appl. Phys. Lett., 2015, 106, 092904; Sheng, J., et al., J. Macromol. Sci. B, 2012, 51, 2093-2104). Obviously, PUA without the addition of polar crosslinks shows poor temperature stability, spanning nearly two orders of magnitude from -40°C to 100°C. This can be attributed to the movement of the polymer chains as the temperature increases. With the introduction of PEGDA, this molecular movement is restricted, thus producing a more stable electromechanical sensitivity over a wide temperature range.
[0261] Example 5. Dynamic performance of DEA of the present invention
[0262] Next the dynamic properties of the as-made DEA of Example 3 were evaluated to understand the effect of including various amounts of PEGDA in the PUA-PEGDA copolymer films.The dynamic properties of the as-made DEA were evaluated as described in General Methods 1.
[0263] Results and Discussion
[0264] DEA prepared from the initial batch of PUA-PEGDA copolymer membranes
[0265] To evaluate the actuation / dynamic properties of the buckled DEA of the present invention, the vertical displacement motion recorded by the laser sensor was first normalized by removing the drift effect from the equilibrium position and taking the average displacement achieved within 30 cycles. When a voltage was applied to the DEA, the copolymer film sank downward at the overlapping circular area of the electrodes, as shown in Fig.13 The photo of DEA in a is shown.
[0266] Furthermore, the actuator can also be allowed to rise upwards - this can be achieved by using air pressure under the inactive membrane to create a dome shape, thus directing the displacement upwards. Alternatively, the actuator can also be configured to rise upwards without external help (air pressure). This is achieved by using asymmetric electrodes (i.e. made of different materials etc.), whereby the top and bottom electrodes have different mechanical properties. When a voltage is applied, out-of-plane actuation will occur towards the softer side.
[0267] For the copolymer films with different concentrations of PEGDA, the normalized displacements as a function of applied voltage are shown in Fig.14As shown in a. It was observed that with higher applied voltage, larger vertical displacements were achieved. This is due to the larger Maxwell pressure on DEA at higher voltages, which caused larger displacements. In addition, unlike the original PUA film, the PUA-PEGDA copolymer film was tested over 8kV without experiencing dielectric breakdown. When dielectric breakdown occurs, current is able to flow through the polymer film, causing the film to become conductive and unable to actuate. This improvement over DEA using PUA-PEGDA copolymer films can be attributed to the increase in the elastic modulus of the chemically cross-linked copolymer film. For PUA-PEGDA-5 and -10, average displacements of up to 1.5 mm were observed, which is greater than the minimum skin deformation required for detection in a tactile device.
[0268] Furthermore, it was observed that the DEA fabricated from the PUA-PEGDA copolymer film had the smallest actuation drift from equilibrium, which was significantly lower than that of the original PUA ( Fig.13 b and 14b) and VHB polymer (L.Lei, et al., Smart Mater. Struct., 2014, 23, 025037). The minimal actuation drift together with the fast response time can be attributed to the reduction of the viscoelastic properties of the polymer by chemical crosslinking. As chemical crosslinking increases, molecular mobility is limited because it is hindered by adjacent molecules or functional groups, which reduces the viscoelasticity of the copolymer.
[0269] Furthermore, the increase in the elastic modulus suppresses electromechanical instability by preventing excessive thinning of the elastomer, which can lead to dielectric breakdown due to the rapid increase in the electric field across the membrane. This enhancement of the original membrane also resulted in the achievement of vertical displacements of up to 1.5 mm. To quantify the response time of the actuator, the time taken to reach 90% of the maximum peak for each cycle was recorded. Further, the creep recovery time was determined as the time taken to reach 90% of the minimum value for each cycle. From Fig.15 From the individual cycle distributions in a, the PUA-PEGDA copolymer films showed significant improvements in response and recovery times, with PUA-PEGDA-10 achieving the fastest speeds of 0.66s and 0.69s, respectively. This represents a huge improvement over the original PUA film, where the response and recovery times were approximately 3.5s and 4.0s, respectively, while the commonly used VHB polymer had a strain response that continued to increase after 3min. Notably, the response and recovery times of PUA-PEGDA-5 were improved by at least five times compared to the original PUA ( Fig.15 b).
[0270] DEA made from subsequent batches of PUA-PEGDA copolymer membranes
[0271] The dynamic performance and durability of buckling mode DEAs fabricated from subsequent batches of PUA-PEGDA copolymer membranes were evaluated by cyclic testing at 0.5 Hz for 1050 cycles. To evaluate the effect of viscoelastic drift, the first 145 buckling cycles of all the above DEAs were studied ( Fig.16 ad). Subsequent cycles in Fig.17 ah is shown. It is observed that DEA made with PUA and PUA-PEGDA-5 gradually drifts a large amount (>0.15mm) from its equilibrium position before reaching a stable state. Such behavior is the result of the intrinsic viscoelastic properties of the film, in which the relaxation time is slower than the cycle time, and energy is dissipated by the polymer chains sliding laterally from each other. Similar behavior has been observed in elastomers with high viscoelasticity (such as VHB polymers).
[0272] PEGDA was introduced as a chemical cross-link, which anchored the polymer chains to reduce molecular motion, leading to better thermal stability ( Fig.12 ), faster relaxation times and minimal DEA drift. These findings are Fig.16 It is obvious in ad, which shows that the viscoelastic drift of the PUA-PEGDA-15 sample is significantly reduced compared to the viscoelastic drift of PUA. At the end of 145 cycles, PUA drifted a distance of 0.28mm from its initial starting point, while PUA-PEGDA-15 drifted a distance of only 0.09mm. With the reduction of viscoelastic drift, better positioning accuracy can be obtained.
[0273] In addition, by adjusting the viscoelastic properties of the polymer film, the response time of the actuator can also be controlled. In order to allow sufficient time to reach the peak displacement, the voltage was applied at 0.1 Hz. The response time of the actuator t 0.9 is quantified as the time taken to reach 90% of the maximum displacement per cycle. Fig.16 From the above, the response time achieved by PUA-PEGDA-15 is less than one second, which is an improvement compared to PUA. This finding is also confirmed by the reduced hysteresis loss tested (Example 2, Figure 7 ). Strain response of as-synthesized PUA-PEGDA-15 ( Fig.16 e) Strain response similar to silicone with higher elastic properties, lower dissipated energy and faster response time.
[0274] As described above, the response time achieved by the PUA-PEGDA materials disclosed herein can be reduced by more than 50% compared to PUA alone. Considering that 90% of the maximum amplitude can be reached in less than one second, together with stable and reliable performance (due to the significant reduction of viscoelastic drift with increasing PEGDA concentration), the flexure actuators are allowed to be used in a wide range of high-precision applications. These include, but are not limited to, tunable lenses and gratings.
[0275] Example 6. Properties of DEA mounted on a flexible substrate
[0276] The PUA-PEGDA copolymer was mounted onto a flexible substrate to fabricate a fully flexible DEA ( Fig.18 a). In this study, as-synthesized PUA-PEGDA-10 copolymer films were used, whereas polyethylene terephthalate (PET) substrates were used as substrates 30 (in Figure 8 b). Nevertheless, it should be noted that the DEA will be able to operate without a substrate. Typically, a PET substrate with holes larger than the electrode area but smaller than the dielectric elastomer is used to mount the DEA. The holes are created to prevent inhibition of the vertical displacement of the DEA during actuation. The dielectric elastomer layer is adhered to the substrate using tape (3M VHB Tape F9473PC).
[0277] like Fig.18 As shown in Figure c, the as-fabricated DEA was subjected to various bending radii ranging from about -6 cm (bending downward) and up to 7 cm (bending upward). Fig.18 c, the actuator was observed to remain functional within 30 cycles, with minimal drift from its equilibrium position, and exhibited stable actuation. Surprisingly, although the PUA-PEGDA-10 copolymer film was bent upward, it continued to bend downward, which is different from the report of using geometric supports to generate pre-bends to promote uniaxial buckling (R. Vertechy, et al., Smart Mater. Struct., 2012, 21, 094005). In addition, from Fig.18 b, based on the normalized displacement within 30 cycles, the bending radius was found to have minimal degradation to the device performance, with the maximum displacement found from the test sample reduced by about 30% after continuous cycling. In addition, the actuator can also be allowed to rise upward by using air pressure under the inactive membrane to create a dome shape, which directs the displacement upward, or as described in Example 5 above. Therefore, the PUA-PEGDA copolymer film and DEA configuration were proven to be highly stable and mechanically deformable, making them highly suitable for shaping for soft robotic applications.
[0278] The above demonstrates the use of PUA-PEGDA copolymers in a flexure actuator without rigid components by mounting the copolymers on a flexible PET substrate. Further, out-of-plane actuation is still observed when the substrate is bent, suggesting the potential use of such actuators in haptic devices.
[0279] Example 7. Fabrication of a Dielectric Elastomer Actuator Array with Selective Actuation and Its Integration into a Wearable Device
[0280] Previous Examples 3-6 have demonstrated the fabrication of DEAs that provide actuation at a single local area. To demonstrate the feasibility of actuation at selected multiple points, a DEA array was fabricated that included an array of electrodes ( Fig.19 a and b).
[0281] In such Fig.19 In the setup shown in a and b, three carbon grease electrodes (42, 44) are applied to each of the top and bottom surfaces of the PUA-PEGDA copolymer film (46) such that the top and bottom electrodes are perpendicular to each other. To provide selective actuation, the top three electrodes (42) and the middle electrode at the bottom are connected to a current source (50) via electrical connections (48). The overlapping region at 52 is the electrically active region where current is applied and actuation can occur. In addition, as shown in FIG. Fig.19 As shown in c, a fabricated actuator array with a cross-junction configuration can be fabricated on a flexible PET substrate (without a rigid frame or pre-stretching).
[0282] In addition, Fig. 20 Figures ac show the integration of the fabricated actuator array into a watch strap to provide tactile feedback for a wearable device. Fig. 20 b. This arrangement is similar to Fig.19 b, but with four top electrodes (42) and two bottom electrodes (44), and wherein electrical connections (48) are made to selected electrodes.
[0283] Example 8. Fabrication of a Transparent Dielectric Elastomer Actuator (DEA) Using Silver Nanowires as Electrodes
[0284] In addition to using carbon grease as an electrode, silver nanowires are also used as electrodes for the manufacture of DEA of the present invention.
[0285] Typically, silver nanowires (dispersed in isopropanol) with an average diameter of 50 nm and a length of 100-200 μm at a concentration of 0.5 mg / mL were spray coated onto the PUA-PEGDA copolymer films on the top and bottom surfaces.
[0286] A photograph of the device under actuation is shown in Fig.21 a, while the performance of the transparent actuator is shown in Fig.21 b. The transparent device exhibits greater actuation characteristics (i.e., displacement) compared to the actuator coated with carbon grease electrodes ( Fig.21 b contrast Fig.13 b) This is most likely due to the lighter weight and higher conductivity of the spray-coated silver nanowire electrodes compared to the carbon grease electrodes, which provides a more efficient electric field distribution across the membrane, thus enhancing the performance of DEA.
[0287] from Fig.21 From the graph of the a, it was observed that the silver nanowire electrodes were generally transparent (with good optical transmittance), which may be useful for integrating DEA into wearable devices as the electrodes would be less noticeable (compared to carbon grease electrodes). Further, such transparent electrodes provide less optical interference to other optical techniques and may allow other features requiring light to be easily integrated into DEA or wearable devices. The optical transmittance of PUA-PEGDA copolymer films with and without silver nanowires as a function of wavelength in the visible light range of 400-800 nm is Fig.21 c. Using spray-coated silver nanowires, the fabricated transparent DEA exhibited an average optical transmittance of 62.7% (a decrease of about 19% compared to the PUA-PEGDA copolymer film without electrodes).
[0288] Example 9. Using different number average molecular weight (M n Comparison of mechanical properties of as-synthesized PUA-PEGDA copolymer membranes made with PEGDA
[0289] In order to understand the number average molecular weight (M) of PEGDA n ) on the mechanical properties of PUA-PEGDA copolymer films. n PUA-PEGDA copolymer membranes were fabricated with 575 and 2000 Dalton PEGDA. In this study, the amount of PEGDA was kept at 15 wt %, and the membranes with M n The copolymer membranes synthesized with PEGDA of 575 and 2000 Daltons were denoted as "PUA-PEGDA-15" and "PUA-PEGDA(2000)-15", respectively.
[0290] experiment
[0291] The PUA-PEGDA-15 copolymer membrane was synthesized according to the method described in Example 1. For PUA-PEGDA (2000)-15, PUA (CN9021) was firstly mixed with 15 wt% PEGDA (M n =2000 Daltons) was mixed, and then 1 wt% AIBN was added, wherein the mixture was mixed thoroughly. To ensure that PEGDA was dissolved and mixed with CN9021, acetone was added to the mixture in a weight ratio of 1:2 (CN9021:acetone) and stirred. Thereafter, the mixture was cast, degassed and finally heated at 90°C for 1 hr under an inert environment. Tensile testing was performed as described in Example 2, wherein the strain rate was 3.33 mm s -1 .
[0292] Results and Discussion
[0293] like Fig. 22 As shown in the figure, when using different M n The mechanical properties of the PUA-PEGDA copolymer films differ significantly when the PEGDA is added. When compared to PUA-PEGDA-15 and PUA, PUA-PEGDA (2000)-15 clearly shows a decrease in modulus, indicating the formation of a softer material. The difference in modulus can be attributed to the fact that the same amount of PEGDA with PUA-PEGDA (2000)-15 is not as effective as with PUA-PEGDA (2000)-15. n Compared with PEGDA (575 Daltons), PEGDA (M n 2000 Daltons) is reduced. Thus, this reduces the number of reactive acrylate groups in PEGDA (which has a higher M n ) acts as a crosslinking agent, and thus cannot reduce the viscoelasticity of the dielectric elastomer. In view of this, it is preferred to use n (i.e., 200 to 1000 Daltons) of PEGDA. n The mechanical properties of the as-synthesized polymer films fabricated with PEGDA are shown in Table 4.
[0294] Table 4. n )'s PEGDA and the mechanical properties of as-synthesized PUA-PEGDA copolymer films made with PEGDA.
[0295]
[0296] a Apparent modulus at 10% strain calculated from the stress-strain curve.
[0297] b The apparent modulus at 50% strain calculated from the stress-strain curve.
Claims
1. A buckling actuator comprising: a first electrode; a second electrode; as well as A dielectric elastomer material film having a first surface and a second surface sandwiched between the first and second electrodes, the material being formed by random block copolymerization of: a polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups, and the polymeric material having a number average molecular weight greater than 20,000 Daltons; as well as a polar polymeric material having a number average molecular weight of 200 to 1,000 Daltons and selected from one or more of poly(trimethylolpropane triacrylate-co-ethylene dimethacrylate), poly(ethylene glycol) diacrylate (PEGDA), poly(caprolactone) dimethacrylate, and poly(propylene glycol) dimethacrylate, in: The first electrode is arranged to cover a first electrode area on the first surface of the dielectric elastomer material film, and the second electrode is arranged to cover a second electrode area on the second surface of the dielectric elastomer material film, so that there is an overlapping area between the first and second electrode areas, and the area has an area smaller than the area of the first or second surface of the dielectric elastomer material film.
2. The actuator according to claim 1, wherein: The first and second electrode areas each occupy 5% to 50% of the area on the first and second surfaces of the dielectric elastomer material film, respectively.
3. An actuator according to claim 1 or claim 2, wherein: (a) The polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl terminal groups has two acrylate terminal groups.
4. The actuator according to claim 1, wherein: The polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl terminal groups is selected from one or more of the following: a urethane acrylate polymer material having two acrylate terminal groups, poly(dimethylsiloxane) dimethacrylate, and a thermoplastic polyurethane having two acrylate terminal groups.
5. The actuator according to claim 4, wherein: The urethane acrylate polymer material having two acrylate end groups is selected from one or more of CN310, CN8881, CN8884, CN8888, CN9004, CN9014, CN9028, CN9031, CN9002, CN966J75, CN9018, CN9021, CN3108, CN3211 and CN8004.
6. The actuator according to claim 1, wherein: The polar polymer material having two or more acrylate or vinyl end groups is poly(ethylene glycol) diacrylate (PEGDA).
7. The actuator according to claim 1, wherein: The polar polymer material having two or more acrylate or vinyl end groups has a number average molecular weight of 250 to 750 Daltons.
8. The actuator according to claim 1, wherein: The polar polymer material having two or more acrylate or vinyl terminal groups is present in the dielectric elastomeric material in an amount of 5 to 15 wt %.
9. The actuator according to claim 1, wherein: (aa) The dielectric elastomer material has a dielectric constant (ε r ) is greater than 3; and / or (ab) the dielectric elastomeric material has an elastic modulus of 0.1 to 4 MPa; and / or (ac) the flexure actuator has a displacement less than or equal to 1,250 μm when a voltage is supplied to the first and second electrodes; and / or (ad) the dielectric elastomeric material has a dielectric breakdown less than or equal to 30 V / µm; and / or (ae) The dielectric elastomeric material has an elongation at break greater than 50%.
10. The actuator according to claim 1, wherein: The actuator further includes a flexible substrate, wherein the second electrode is placed on the flexible substrate, and the dielectric elastomer material film is formed on top of the flexible substrate and at least a portion of the second electrode.
11. The actuator according to claim 1, wherein: The actuator does not include a rigid constraining member.
12. The actuator according to claim 1, wherein: The first and second electrodes are independently selected from carbon esters, one or more metal nanowires, hydrogels, ion gels, carbon nanotubes and liquid metals.
13. The actuator according to claim 1, wherein: The actuator is transparent.
14. A dielectric elastomeric material formed by random block copolymerization of: a polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups and having a number average molecular weight greater than 20,000 Daltons; and A polar polymer material having a number average molecular weight of 200 to 1,000 Daltons and selected from one or more of poly(trimethylolpropane triacrylate-co-ethylene dimethacrylate), poly(ethylene glycol) diacrylate (PEGDA), poly(caprolactone) dimethacrylate, and poly(propylene glycol) dimethacrylate.
15. The dielectric elastomer material of claim 14, wherein: (ai) The polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl terminal groups has two acrylate terminal groups.
16. The dielectric elastomer material according to claim 14, wherein The polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl terminal groups is selected from one or more of the following: a urethane acrylate polymer material having two acrylate terminal groups, poly(dimethylsiloxane) dimethacrylate, and a thermoplastic polyurethane having two acrylate terminal groups.
17. The dielectric elastomer material according to claim 14, wherein The urethane acrylate polymer material having two acrylate end groups is selected from one or more of CN310, CN8881, CN8884, CN8888, CN9004, CN9014, CN9028, CN9031, CN9002, CN966J75, CN9018, CN9021, CN3108, CN3211 and CN8004.
18. The dielectric elastomer material according to claim 14, wherein The polar polymer material having two or more acrylate or vinyl end groups is poly(ethylene glycol) diacrylate (PEGDA).
19. The dielectric elastomer material according to claim 14, wherein The polar polymer material having two or more acrylate or vinyl end groups has a number average molecular weight of 250 to 750 Daltons.
20. The dielectric elastomer material of claim 14, wherein: The polar polymer material is present in the dielectric elastomeric material in an amount of 5 to 15 wt %.
21. The dielectric elastomer material of claim 14, wherein: (Aa) The dielectric elastomer material has a dielectric constant (ε r ) is greater than 3; and / or (Ab) the dielectric elastomeric material has an elastic modulus of 0.1 to 4 MPa; and / or (Ac) the dielectric elastomer material is provided in the form of a film; and / or (Ad) the dielectric elastomeric material has a dielectric breakdown less than or equal to 30 V / µm; and / or (Ae) The dielectric elastomeric material has an elongation at break greater than 50%.
22. A method of forming the dielectric elastomer material of claim 14, the method comprising the steps of: (i) providing a mixture comprising a polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups and a polar polymer material in the presence of a free radical initiator, the polar polymer material having a number average molecular weight of 200 to 1,000 Daltons and selected from one or more of the following: poly(trimethylolpropane triacrylate-co-ethylene dimethacrylate), poly(ethylene glycol) diacrylate (PEGDA), poly(caprolactone) dimethacrylate, and poly(propylene glycol) dimethacrylate, wherein the polymer material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups has a number average molecular weight greater than 20,000 Daltons; and (ii) reacting the mixture at an elevated temperature for a period of time to provide the dielectric elastomeric material.
23. The method of claim 22, wherein: (ia) The polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl terminal groups has two acrylate terminal groups.
24. The method according to claim 22, wherein: The polymer material including silicon or nitrogen atoms having two or more acrylate or vinyl terminal groups is selected from one or more of the following: a urethane acrylate polymer material having two acrylate terminal groups, poly(dimethylsiloxane) dimethacrylate, and a thermoplastic polyurethane having two acrylate terminal groups.
25. The method according to claim 22, wherein: The urethane acrylate polymer material having two acrylate end groups is selected from one or more of CN310, CN8881, CN8884, CN8888, CN9004, CN9014, CN9028, CN9031, CN9002, CN966J75, CN9018, CN9021, CN3108, CN3211 and CN8004.
26. The method of claim 22, wherein: The polar polymer material having two or more acrylate or vinyl end groups is poly(ethylene glycol) diacrylate (PEGDA).
27. The method of claim 22, wherein: The polar polymer material having two or more acrylate or vinyl end groups has a number average molecular weight of 250 to 750 Daltons.
28. The method of claim 22, wherein: The polar polymer material having two or more acrylate or vinyl terminal groups is present in the dielectric elastomeric material in an amount of 5 to 15 wt %.
29. The method of claim 22, wherein: After completion of step (ii) of claim 22, the dielectric elastomer material is provided in the form of a film.
30. The method of claim 22, wherein: The mixture of step (i) of claim 22 further comprises a solvent, wherein the solvent and the polymeric material comprising silicon or nitrogen atoms having two or more acrylate or vinyl end groups have a weight to weight ratio of 10:1 to 1:
1.
31. The method of claim 22, wherein: (A) the elevated temperature in step (ii) of claim 22 is 50 to 100°C; (B) the free radical initiator is present in an amount of at least 1 wt % of the mixture; (C) The reaction in step (ii) of claim 22 is carried out over a period of 10 minutes to 24 hours.
32. An array of buckling actuators, comprising a plurality of buckling actuators according to any one of claims 1 to 13.
33. An array of buckling actuators according to claim 32, wherein: The array of buckling actuators is arranged in a cross-knot configuration.
Citation Information
Patent Citations
Hydraulic transfer film and process for producing hydraulic transfer product therewith
US20060073342A1
Cross-linkable thermoplastic polyurethanes
US20090197000A1
Electroactive polymers and systems using the same
US20170333223A1
Electroactive polymers that contract and expand, sense pressure, and attenuate force and systems using the same
WO2017223424A1